A survey on current management of patients with mild (Stage 1) hypertension by physicians in Metro Cebu towards the formulation of practice guidelines - Quiza, Ma. Fidelis E.
Because over 90 of hypertensive patients are in the mild to moderate range with 50 classified as having mild or Stage I Hypertension, this group of patients accounts for a major proportion of the excess risk in terms of morbidity, disability and mortality attributable to hypertension. Despite the disproportionately larger risk for the population at large from Stage I Hypertension, therapy of all patients with Stage I Hypertension is only marginally cost effective relative to treatment of patients with Stage 2 - Stage 4 Hypertension.To describe the current practices and the determinants to the various practice patterns in the management of patients with mild or Stage I Hypertension and compare these with standards recommended in literature.All licensed physicians who have been in active practice since at least 1992 to the present time of the conduct of the survey regardless of type of practice, or affiliation and who actively manage adult patients with hypertension in Metro Cebu.A structured questionnaire was formulated based on focus group discussions and hypertension consensus guideline recommendations. After pre-testing, the 31-item questionnaire was delivered to identified subjects in Metro Cebu.Main outcome meausres (1) Case definition, evaluation, treatment and follow-up of patients with Stage I Hypertension, (2) drug utilization patterns in the management of patients with Stage I Hypertension, (3) determinants to the selection of interventional strategies (4) physician's rating of the adequacy of control of Stage I Hypertension in their respective practices, (5) deviant practice patterns based on JNC VI and Philippine Multisectoral Task Force guidelines (6) perceived barriers to adequacy of hypertension control as reported by the respondents and descriptive statistics using measures of central tendency and dispersion for continuous variables and frequency or proportion for categorial variables. Univariate analysis used to determine significant relationships between physician-related independent variables and practice patterns or to explain differences in outcome were carried out using the Chi-Square test for categorial variables and the nonparametric tests such as Mann-Whitney-U Test and the Kruskall Wallis 1-Way ANOVA for continuous variables. A logistic regression analysis using forward selection with likelihood-ratio criterion was done to determine for significant relationships between variables entered as covariates.A total of 354 questionnaires were sent and 228 returned forms were analyzed for a total response rate of 64.4.The questionnaire took 35.7 +-8.2 minutes to complete. Clinic prevalence of hypertension ranged from less than 10 to 40. Stage I Hypertension prevalence was up to 60 of total hypertension seen in practice. BP control was judge adequate for at most 30 of patients with hypertension. Some respondents claimed adequate control in less than 10 of patients with Stage I Hypertension, whereas other respondents claim adequate control in 80 -90 of the same group of patients. A difference in response was attributed to a difference in the type of practice area of specialization.Majority of the respondents correctly defined 140 mm Hg and 90 mm Hg as the lower limits of systolic and diastolic BP, respectively for Stage I Hypertension.
Only 40 of the respondents correctly defined 159 mm Hg as the upper limits of systolic and diastolic BP, respectively. Blood pressires are read to the nearest 5 mm Hg or rounded off the nearest 10 mm Hg and the diagnosis is confirmed after at least two visits by majority of the respondents. Korotkoff phase I is associated with systolic BP by the majority of the respondents but only 50 identify diastolic BP with Korotkoff phase 5. Years of practice and training at the time of survey explained some of the difference in responses. At least 50 of the respondents will routinely request for lipid profile and fasting blood glucose in the evaluation of cardiovascular risk factors and ECG, serum creatinine determination and urinalysis in the evaluation of target organ damage. Other procedures recommended as routine in the JNC VI were not considered extremely important by the majority of the respondents. Diastolic BP, cardiovascular symptoms and patients finances were important determinants to the choice of laboratory procedures.Contrary guideline recommendations, not all of the respondents (56) will start with lifestyle modification alone. However, lifestyle modification strategies most commonly advised are consistent with guideline recommendations which include weight reduction, cessation of smoking, salt restriction, reduction of alcohol intake and regular exercise. Lifestyle modification is perceived to be effective in controlling elevated BP in only up to 20 of patients by majority of the respondents. Most physicians will wait up to 2 months before adding drug therapy for persistently elevated BP. Drug therapy will either be a calcium channel blocker, a beta-blocker or an ACE inhibition for the majority of the respondents.Biomedical factors such as diastolic BP, signs of target organ damage particularly the heart and the kidney and concurrent cardiovascular risk factors are extremely important determinants to the choice of treatment for patients with Stage I Hypertension. Physician-related characteristics, patient-related characteristics and drug-related characteristics are also influential in the choice of a particular treatment modality.The same physician-related characteristics, patient-related characteristics and drug-related characteristics that influence choice of treatment were cited as extremely important barriers to adequate BP control. Modifiable factors that could be the target of educational strategies such as patient understanding and physician understagding of the illness and the treatment were particularly important.Local physicians relied heavily on personal experience with the drug and actual patient response as sources of information regarding management of patients with Stage I Hypertension. Other sources deemed helpful were journal articles, conferences and consensus guidelines. On the whole, majority of the physicians are confident that their management is appropriate and in the best interest of the patient.There is variation in the practice of physicians in Metro Cebu regarding management of patients with Stage I Hyperteion. Variations were noted for case definition and confirmation of diagnosis, evaluation and treatment. Not all physicians had practice patterns similar to guideline recommendations. Practice behavior and clinical-decision making of local physicians in Metro Cebu regarding management of patients with Stage I Hypertension is influenced by a combination of biomedical influences, patient-related characteristics, physician-related characteristics and drug or procedure-related characteristics. Selection of a particular evaluation procedure or treatment modality is dependent on diastolic BP and absolute cardiovascular risks for the majority of the respondents.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Hypertension; Hypertensive patients